2019
DOI: 10.1080/15384101.2019.1577665
|View full text |Cite|
|
Sign up to set email alerts
|

CDK11p110 plays a critical role in the tumorigenicity of esophageal squamous cell carcinoma cells and is a potential drug target

Abstract: Esophageal squamous cell carcinoma (ESCC) is a serious malignancy with limited options for targeted therapy. The exploration of novel targeted therapies for combating ESCC is urgently needed. Cyclindependent kinases (CDKs) play important roles in the progression of cancers; however, the function of CDK11 p110 (cyclin-dependent kinase 11 p110) in ESCC is still unknown. Here, we investigated the effects and molecular mechanisms of CDK11 p110 in the proliferation and growth of ESCC by examining the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…We also observed increased G1-phase cells after CDK11 knockdown, similar to what was reported in breast cancer, another epithelial cancer [13]. In contrast, CDK11 knockdown in esophageal squamous cell carcinoma cells induced G2/M accumulation [56]. CDK11 and Cyclin L1 were recently reported to regulate the cell cycle in non-transformed Bombyx mori (silkworm) cells.…”
Section: Discussionsupporting
confidence: 85%
“…We also observed increased G1-phase cells after CDK11 knockdown, similar to what was reported in breast cancer, another epithelial cancer [13]. In contrast, CDK11 knockdown in esophageal squamous cell carcinoma cells induced G2/M accumulation [56]. CDK11 and Cyclin L1 were recently reported to regulate the cell cycle in non-transformed Bombyx mori (silkworm) cells.…”
Section: Discussionsupporting
confidence: 85%
“…The CDK11-p110 (known as CDC2L2, CDC2L3, p58GTA, PITSLRE, CDK11-p46, or CDK11-p58) regulates cell proliferation. Downregulation of this protein has been shown to induce cell cycle arrest at G1 phase in human breast cancer cells (Zhou et al, 2015), and at G2/M phase in esophageal squamous cell carcinoma (Du et al, 2019). Moreover, the induction of apoptosis in esophageal squamous cell carcinoma was observed when CDK11-p110 was inhibited by RNA interference (Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of this protein has been shown to induce cell cycle arrest at G1 phase in human breast cancer cells (Zhou et al, 2015), and at G2/M phase in esophageal squamous cell carcinoma (Du et al, 2019). Moreover, the induction of apoptosis in esophageal squamous cell carcinoma was observed when CDK11-p110 was inhibited by RNA interference (Du et al, 2019). In the present study, the active form of vitamin B3, nicotinamide (known as niacinamide), was shown to be the metabolite that is linked with the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…3 The over-expression of CDKs is closely related to the development of tumors. For example, the up-regulation of CDK2, CDK4, CDK6, CDK8, and CDK11 is positively correlated with the occurrence and deterioration of breast cancer, 4 rectal cancer, 5 esophageal cancer, 6 and so on. CDKs have been considered as promising targets for the treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%